Unprotected Left Main Coronary Artery Percutaneous Coronary Intervention-Our Experiences at a Tertiary Hospital (Cardiovascular Journal, 2014)
Background: Aim of the study was to evaluate the primary procedural success of percutaneous coronary intervention of unprotected left main coronary artery stenosis using either Bare-metal stents or drug eluting stent. Methods: Total 33 patients were enrolled in this very preliminary non-randomized prospective cohort study. Among them, Male: 25 and Female: 8. Total 35 stents were deployed. Mean age were for Male: 59 yrs, for Female: 62 yrs. Associated coronary artery diseases risk factors were dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive family history for coronary artery diseases and smoking. Results: Among the study group; 26 (78%) were Dyslipidemic, 24(70%) were hypertensive; 17 (51.5%) patients were Diabetic, 11(33%) were smoker and 7(21%) patients had family history of Ischaemic heart disease. Female patients were more obese (BMI M 26: F 27) and developed coronary artery diseases in advance age. Common stented territory were left main: 20 (60%), Left main to left anterior descending artery 7 (22%) and Left main to left circumflex artery 6 (18%). Average length and diameter of stent was 3.5 and 18 mm respectively. Stent used: Bare Metal Stent 5 (15%), Drug Eluting Stent: 28 (85%). Among the different Drug Eluting Stents, Everolimus eluting stents were 11 (39.3%), Sirolimus eluting 10(35.7%), Paclitaxel eluting 3 (10.7%), Biolimus eluting 3 (10.7%) and Zotarolimus eluting1 (3.6%). In the present study, overall survival outcome was 94% (31 patient), mortality of cardiac cause 3% (1 patient) and 1 patient (3%) died of hepatocellular carcinoma. Conclusion: Our study has shown that percutaneous coronary intervention of the unprotected left main is a safe and effective alternative to Coronary Artery Bypass Graft (CABG). DOI: http://dx.doi.org/10.3329/cardio.v6i2.18349 Cardiovasc. j. 2014; 6(2): 107-111